Организация саморегулируемого обучения учащихся в группах с применением теории множественного интеллекта Гарднера - Елисеева, Л.В. (My University, 2016)
The article "The Organization of self-regulated learning of students in the group using the theory of multiple intelligences Gardner's" devoted to the problems of teaching students with low learning motivation. The author shows the possibility of using the theory of Gardner's multiple intelligences in teaching poorly motivated students in the process of organizing group work in class. The main method used in Action Research, whose main purpose is the search for the answer to the question "Is group work an effective method of influence on the motivation learning of students in the classroom?". The article presents a detailed step-by-step algorithm the implementation of the Study. As a result of the conducted Research, the article provides recommendations for teachers having no experience in this area. The author's proposed method contributes to the improvement of educational motivation of students of secondary classes, development of skills of self-regulated learning in groups, is a positive example of implementation of innovative technologies in teaching.
Keywords: innovation; self-regulated learning; theory of multiple intelligences; research in action; group training